Inclusive growth in Syria (Building the indicator and analyzing it for the period 1997-2021) - يوسف محمد; ريم محمود; بشرى علي (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The focus has been on inclusive growth by policy makers and institutions responsible for development and poverty alleviation, such as the Asian Development Bank and the International Monetary Fund, as most countries have included the inclusive growth index in their statistical periodicals and reports as an indicator of the inclusion of marginalized and poorest groups in the process of sustainable economic development. This research presents a framework for measuring the Syrian Inclusive Growth Index based on the indicators chosen by the Asian Development Bank and the Eurasian Economic Union during the period (1997-2021) using Principal Component Analysis (PCA). The Inclusive Growth Index for Syria showed - After its Constructing - a noticeable decline during the period studied, As recorded negative rates during (1997-2000) and (2018-2021), which are the periods corresponding to the economic and political shocks in Syria, which reflects the extent of the structural imbalances within the Syrian economy that increased rates Poverty and inequality in income distribution. Which requires undertaking a set of structural reforms to enhance comprehensive economic growth that reduces inequality social and differences between social groups, and puts the country on a more sustainable development path.